Prospectively evaluating maternal and fetal outcomes in the era of CFTR modulators: the MAYFLOWERS observational clinical trial study design. Issue 1 (16th June 2022) - Jain, Raksha; Magaret, Amalia; Vu, Phuong T; VanDalfsen, Jill M; Keller, Ashley; Wilson, Alexandra; Putman, Melissa S; Mayer-Hamblett, Nicole; Esther Jr, Charles R; Taylor-Cousar, Jennifer L
Abstract : Introduction: Therapeutic advances have markedly increased life expectancy for those with cystic fibrosis (CF), resulting in a median predicted survival over 50 years. Consequently, people with CF (pwCF) are living through their reproductive years and the rate of pregnancy is rapidly rising. Despite the increased relevance of this topic, multicentre studies investigating the association between maternal health and choices made during pregnancy on maternal and fetal outcomes do not exist. Furthermore, there are very limited data on the outcomes following CF transmembrane conductance regulator (CFTR) modulator use during pregnancy and lactation. Methods and analysis: Ma ternal and F eta l O utcomes in the E ra of Modulato rs (MAYFLOWERS) is a prospective, multicentre observational clinical trial which will enrol approximately 285 pregnant pwCF including those who are modulator ineligible and those who choose to continue or discontinue CFTR modulator therapy during pregnancy and lactation. The primary aim of this 35-month study is to assess whether lung function changes during pregnancy differ based on the continued use of modulators or other factors such as pre-existing comorbid conditions. Secondary objectives include evaluation of pregnancy related and obstetrical complications and changes in mental health. Ethics and dissemination: The design of this study required special consideration of study burden on pregnant and lactating people with chronic illness in the setting of a substantial number of unanswered questions under these conditions. MAYFLOWERS is the first prospective clinical trial examining pregnancy in CF; the outcomes will guide providers on pregnancy management in pwCF and others with chronic respiratory disease.